The fear factor : what happens when fear grips Wall Street - Read, Colin, 1959- (Basingstoke, Hampshire : Palgrave MacMillan, 2009)
'The science behind and economic consequences of fear are explained by demonstrating how fear can drive markets to disastrous lows and how the financial industry profits most when fear and volatility are highest. The reader is offered recommendations that can resolve market fears and bolster world economies'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Risk; Fear; Financial crises